Disruptions to HIV prevention during armed conflict in Ukraine and other settings - Nikitin, Benjamin; Bromberg, Daniel J.; Ivasiy, Roman; Madden, Lynn; Machavariani, Eteri; Dvoriak, Sergii; Poole, Danielle N.; Otiashvilli, David; Altice, Frederick L. (Current HIV AIDS reports, 2025)
Purpose of Review: This review evaluates recent literature to understand the ways in which war disrupts HIV prevention andcreates conditions for HIV outbreaks, with a focus on Ukraine. We also examine potential responses that can be deployed to sustain HIV prevention services amid ongoing conflict. Recent Findings: Recent studies and frameworks suggest that disruptions caused during war are comparable to other emergencies, like natural disasters. The most important disruptions included health system/infrastructure destabilization, displacement, and psychological and financial challenges for individuals in key populations. Wars in most settings, as exemplified by the recent war in Ukraine, demonstrate that these disruptions can be tempered through a coordinated, rapid response. Summary: Lesson learned from Ukraine show that adequate preparation and a rapid, collaborative response by providers is needed to ensure HIV prevention during war. Future research should develop comprehensive frameworks outlining how to facilitate this response.
Online veröffentlicht: 14. Dezember 2024
Gesehen am 03.06.2025